[D-Ala2, D-Leu5] Enkephalin Inhibits TLR4/NF-κB Signaling Pathway and Protects Rat Brains against Focal Ischemia-Reperfusion Injury. (12th February 2021) - Fu, Danyun; Liu, Haitong; Zhu, Jiang; Xu, Hongjiao; Yao, Junyan
Abstract : Background . Cerebral ischemia-reperfusion (I/R) injury is the main cause of acute brain injury, which is a life-threatening disease due to the lack of effective treatments. [D-Ala 2, D-Leu 5 ] enkephalin (DADLE) is a synthetic delta-opioid receptor agonist that is reported to confer neuroprotective effect; however, the underlying mechanism is still being explored. The purpose of the present study is to determine whether DADLE administrated intracerebroventricularly could attenuate the cerebral I/R injury, to determine if this is through inhibiting the toll-like receptor 4 (TLR4)/nuclear factor kappa B (NF- κ B) signaling pathway and therefore inhibiting neuroinflammation in an ischemic stroke model. Methods . Rats were subjected to 120 minutes of ischemia by transient middle cerebral artery occlusion (MCAO). At 45 minutes after ischemia, DADLE or control vehicle (artificial cerebrospinal fluid, ACSF) was given to the rats intracerebroventricularly. Neurological deficit, cerebral infarct volume, and histopathological changes were assessed at 24 hours after reperfusion. Brain inflammation was assessed by measuring tumor necrosis factor- α (TNF- α ) and interleukin-6 (IL-6) in the ischemic penumbra by ELISA. The expression of TLR4 was determined by immunohistochemistry staining and western blotting. The expression of NF- κ B was investigated by western blotting. Results . Compared with the vehicle-treatment (ACSF), DADEL improved neurological deficit (9.6 ± 2.1 versus 13.8 ± 1.9 ), reduced cerebral infarct volume (18.74 ± 3.30 % versus 10.57 ± 2.50 % ), and increased the number of normal neurons (29.72 ± 8.53 % versus 51.37 ± 9.18 % ) after cerebral I/R injury in rats (all P < 0.05 ). Expressions of inflammatory molecules including TNF- α and IL-6 were highly expressed in the vehicle-treated rats, whereas treatment with DADLE downregulated these expressions (P < 0.05 ). Additionally, cerebral I/R injury significantly increased the TLR4 and NF- κ B expression in vehicle-control group, which was markedly inhibited by DADLE (P < 0.05 ). Conclusions . DADLE, administrated intracerebroventricularly at 45 minutes after cerebral ischemia, significantly ameliorated I/R-induced brain damage in rats. This kind of neuroprotective effect appears to be related to the downregulation of TLR4-mediated inflammatory responses.